الجريدة الرسمية العدد 41 - رئيس مجلس الوزراء (المطابع الاميرية, 2025)
قرارات رئيس مجلس الوزاء : قرار رقم 2494 لسنة 2024 -- قرار رقم 2495 لسنة 2024 -- قرار رقم 2496 لسنة 2024 -- قرار رقم 2497 لسنة 2024 -- قرار رقم 2498 لسنة 2024 -- قرار رقم 2499 لسنة 2024 -- قرار رقم 2500 لسنة 2024 -- قرار رقم 2887 لسنة 2024